2012
DOI: 10.3109/08880018.2012.693577
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Hematopoietic Stem Cell Transplantation Performed on Thalassemia Major Patients

Abstract: Although successful hematopoietic stem cell transplantation (HSCT) can offer a cure in thalassemia major, there are only a few and noncomprehensive studies of its effect on the quality of life (QoL), as it is expected to increase the QoL by ending transfusion-related issues. Our objective was to compare the health-related quality of life (HRQoL) of transplanted and nontransplanted thalassemia major patients in a developing country. We have studied the QoL effect of HSCT in consecutively invited 50 nontransplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…The majority of the studies that met the inclusion criteria assessed patients with thalassemia (n 5 9, 56.3%), [44][45][46][47][48][49][50][51][52] 1 study covered both thalassemia and SCD patients (n 5 1, 6.25%), 53 and the remaining studies were focused on SCD patients (n 5 6, 37.5%). [54][55][56][57][58][59] A total of 517 patients and/or their parents took part in the included studies and reported HRQOL outcomes [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] ; of these, 101 (19.5%) had SCD [53][54][55][56][57][58][59] and 416 (80.5%) had thalassemia. [44][45][46][47][48][49][50][51][52]…”
Section: Description Of All Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies that met the inclusion criteria assessed patients with thalassemia (n 5 9, 56.3%), [44][45][46][47][48][49][50][51][52] 1 study covered both thalassemia and SCD patients (n 5 1, 6.25%), 53 and the remaining studies were focused on SCD patients (n 5 6, 37.5%). [54][55][56][57][58][59] A total of 517 patients and/or their parents took part in the included studies and reported HRQOL outcomes [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] ; of these, 101 (19.5%) had SCD [53][54][55][56][57][58][59] and 416 (80.5%) had thalassemia. [44][45][46][47][48][49][50][51][52]…”
Section: Description Of All Included Studiesmentioning
confidence: 99%
“…[54][55][56][57][58][59] A total of 517 patients and/or their parents took part in the included studies and reported HRQOL outcomes [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] ; of these, 101 (19.5%) had SCD [53][54][55][56][57][58][59] and 416 (80.5%) had thalassemia. [44][45][46][47][48][49][50][51][52][53] Participants were either patients only (n 5 9, 56.3%), parents or proxy only (n 5 1, 6.3%), or both (n 5 6, 37.5%). Seven studies (43.8%) included both pediatric and adult populations, whereas others included either pediatric (n 5 4, 25%) or adult (n 5 5, 31.3%) ones.…”
Section: Description Of All Included Studiesmentioning
confidence: 99%
“…32 Evaluation of patient-reported HRQOL The PedsQL 4.0 Generic Core Scale is a valid and reliable measure of HRQOL for children with chronic health conditions [33][34][35] and has been used in pediatric HSCT studies. [36][37][38][39][40] HRQOL was assessed using the child selfreported version. The instrument consists of 23 items that measure physical (8 items), emotional (5 items), social (5 items) and school functioning (5 items).…”
Section: Conditioning Regimensmentioning
confidence: 99%
“…Graft-versus-host disease (GVHD) following allogeneic hematopoietic stem cell transplantation (HSCT) is associated with significant morbidity and mortality. 1 Steroids are first-line management, and immunosuppressants such as infliximab, rituximab, and alemtuzumab are second-line. 2,3 Immunosuppression carries significant risks, including infection, reduced graftversus-leukemia effect, and secondary malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Graft‐versus‐host disease (GVHD) following allogeneic hematopoietic stem cell transplantation (HSCT) is associated with significant morbidity and mortality . Steroids are first‐line management, and immunosuppressants such as infliximab, rituximab, and alemtuzumab are second‐line .…”
Section: Introductionmentioning
confidence: 99%